Metode Dakwah Jemaah salafi (studi tentang jemaah salafi riau dan Relevansinya Terhadap Keberlangsungan Kerukunan Umat Beragama) - Muhammad Nurwahid (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2013)
movement launched by Muhammad ibn ‘Abd al-Wahhab. The idea of this update also gives effect to the modern If Hizbu Tahrir typologized as organic because the fundamentalists of Islam as an ideology seat movement